Miloš Zeman and Andrzej Duda – reinventing image for election campaign purposes - Rusin Dybalska, Renata; Budzyńska-Daca, Agnieszka; Rawski, Tomasz (Bohemistyka, 2019)
The aim of this paper is to present a comparative analysis of selected elements of strategies for building political image of Miloš Zeman and Andrzej Duda, applied in the presidential campaign in Poland and Czechia in 2013 and 2015. The paper presents not only basic information about both campaigns, but primarily points to a number of common features, such as main motifs (history, family, the future), the target group and its image, communication channels, all used in both strategies for communicating with voters, despite different PR and cultural sphere of application.